2014
DOI: 10.3389/fpsyg.2014.00825
|View full text |Cite
|
Sign up to set email alerts
|

Toward a dual-learning systems model of speech category learning

Abstract: More than two decades of work in vision posits the existence of dual-learning systems of category learning. The reflective system uses working memory to develop and test rules for classifying in an explicit fashion, while the reflexive system operates by implicitly associating perception with actions that lead to reinforcement. Dual-learning systems models hypothesize that in learning natural categories, learners initially use the reflective system and, with practice, transfer control to the reflexive system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(96 citation statements)
references
References 150 publications
(213 reference statements)
6
90
0
Order By: Relevance
“…In the visual domain, it has been suggested that full feedback discourages learners from switching to using inseparable boundaries, rather than separable boundaries, to approximate the category structure (Maddox et al, 2008). The disruptive effect of full feedback has been replicated in speech category learning, where the optimal decision boundaries are posited to be inseparable (Chandrasekaran et al, 2014a;Chandrasekaran et al, 2014b;Maddox and Chandrasekaran, 2014). One possible explanation for the equivalent performance between full and minimal feedback conditions in the auditory domain is that the learners were less likely to be initially biased towards using separable boundaries, when learning less easily verbalizable non-speech auditory categories than with speech auditory categories.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In the visual domain, it has been suggested that full feedback discourages learners from switching to using inseparable boundaries, rather than separable boundaries, to approximate the category structure (Maddox et al, 2008). The disruptive effect of full feedback has been replicated in speech category learning, where the optimal decision boundaries are posited to be inseparable (Chandrasekaran et al, 2014a;Chandrasekaran et al, 2014b;Maddox and Chandrasekaran, 2014). One possible explanation for the equivalent performance between full and minimal feedback conditions in the auditory domain is that the learners were less likely to be initially biased towards using separable boundaries, when learning less easily verbalizable non-speech auditory categories than with speech auditory categories.…”
Section: Discussionmentioning
confidence: 88%
“…When participants learn Mandarin Chinese lexical tone categories, where the optimal decision boundaries are posited to be inseparable (Chandrasekaran et al, 2010;Maddox and Chandrasekaran, 2014;Chandrasekaran et al, 2014a), adult learners initially attempt to identify the tone categories using separable boundaries but gradually transition to using inseparable boundaries (Maddox and Chandrasekaran, 2014;Chandrasekaran et al, 2014a). Minimal feedback, relative to full feedback, leads to faster learning (Chandrasekaran et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…We predict that explicit instruction to the pitch direction dimension will speed the transition from simple unidimensional reflective, rule-based strategies (e.g. rules related to pitch height) to a more optimal reflexive strategy that weights both dimensions (equally) during decision (Chandrasekaran, et al, 2014a; Maddox & Chandrasekaran, 2014a; Maddox, Chandrasekaran, Smayda, & Yi, 2013; Maddox et al, 2014). …”
Section: Overviewmentioning
confidence: 99%
“…DLS assumes that speech category learning involves a competition between a reflective system that is rule-based and relies on executive function processes in the prefrontal cortex, and a reflexive system that is procedural and relies upon dopamine-mediated reward signals in the striatum (Chandrasekaran, et al, 2014a; Maddox & Chandrasekaran, 2014a; Yi, Maddox, Mumford, & Chandrasekaran, 2014) 1 . The DLS approach derives from Ashby and Townsend's (1986) General Recognition Theory that is a multidimensional extension of signal detection theory (Green & Swets, 1967).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation